Paraglacial Rock Slope Stability Under Changing Environmental Conditions, Safuna Lakes, Cordillera Blanca Peru - Klimeš, Jan; Novotný, Jan; Rapre, Alejo Cochacin; Balek, Jan; Zahradníček, Pavel; Strozzi, Tazio; Sana, Hamid; Frey, Holger; René, Miloš; Štěpánek, Petr; Meitner, Jan; Junghardt, Johan (Frontiers in Earth Science, 2021)
Landslides or landslide-induced impact waves in high mountain lakes represent high hazard for society calling for realistic assessment of rock slope stability responsible for the process chain initiation. This task is often hampered by complex interplay of triggers, which effects on slope stability may be delayed by decades or even millennia, while historical records describing slope topography or landslide occurrences are usually shorter and incomplete. This article builds on rarely available detailed historical data describing site of the 2002 rock avalanche in the Cordillera Blanca, Peru. It caused dangerous impact wave in the Safuna Alta Lake resulting into minor flood, but ongoing downstream development significantly increased possible negative effects of comparable event. Pre- and post-2002 failure slope topography, 70 years long history of glaciation and landslide occurrences were combined with non-invasive field geological survey and laboratory geotechnical analysis to characterize the distinct morphological parts of the failed slope with reliable engineering geological slope models. Their stability was calculated for series of environmental scenarios providing insights into the 2002 rock avalanche failure mechanism and dynamics as well as role of glacier slope support for its stability. Results show that the rock slope stability is governed by discontinuous slip planes where the rock bridges represent the most likely additional resisting forces. The effect of glacier support on the slope stability is limited under full-water saturation of the rocks and due to specific morpho-structural conditions. Importance of the long-term, progressive deterioration of the rock slope strength under paraglacial environment and repeated seismic shaking is illustrated by the fact that even the LIA maximum glacier extend had only minor positive effect on the pre-2002 rock avalanche slope stability. Despite of that, the slope remained without major failure for decades or possibly even centuries. Its collapse in 2002 caused retrogressive movements of the adjacent slope, which remains highly unstable until now. We suggest that considerable longer time would be needed to produce major rock slope failure directly above the lake possibly triggering highly hazardous impact wave. Therefore the future safety of the lake would largely benefit from implementation of reliable slope movement monitoring system.